Zerumbone induces cytotoxicity and inhibits cell migration of human colon cancer cells - Tan, Min Jien; Siti Nur Parvin Ab Hamid,; Nur Fariesha Md Hashim,; Nurdin Armania,; Hasni Idayu Saidi,; Noraina Muhamad Zakuan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Colon cancer is the second leading cause of cancer death among males and females. Survival in colorectal cancer patients is poor and greatly affected by its metastasis. Zerumbone (ZER) is an active compound isolated from the essential volatile oil of an edible ginger plant, Zingiber zerumbet. It is known to exhibit anticancer properties which able to inhibit cancer cell proliferation and induce apoptosis in colon cancer. These findings led us to investigate the ability of ZER to inhibit cell migration in colon cancer cell line. From the MTT results, the IC50 values for HCT116 cells treated with ZER were 8.9 ± 0.3, 18.0 ± 1.2, and 21.3 ± 3.5 µg/mL at 24, 48, and 72 h of incubation, respectively. The results show that the IC 50 was significantly increased (p <0.05) in a time-dependent manner. The treatment of ZER at higher concentration (6 and 9 µg/mL) inhibited the migration of HCT116 cells at 1.5-fold higher compared to that of the untreated cells which reduced in the scratch gap. The characteristic of apoptosis such as cell shrinkage, membrane blabbing, and detachment of cells were observed on HCT116 cells treated with ZER, suggesting that the mode cell death induced by ZER on HCT116 cells might be due to apoptosis. Hence, it is concluded that ZER exhibits cytotoxic effects and inhibits cell migration in colon cancer cells.